Analysis and Optimization on Vibration Characteristics of Twin Screw Pump. Issue 5 (January 2021) - Zhong, Yan; Zhou, Pu; Fu, Dongliang; Lu, Zhen
Abstract: Based on double screw pump as the research object, the vibration of twin screw pump under different outlet conditions and different technological parameters were tested. The vibration characters of the pump under various technological parameters were analyzed from the experimental point of view. The key parameters influencing the vibration characteristic of twin screw pump were found out and corresponding optimization measures were taken. By using the numerical method of fluid mechanics, the three-dimensional flow field inside the pump chamber was analyzed, and the internal working mechanistic and influencing factors were discussed. Local optimization was carried out to reduce the influence of fluid excitation force on structure vibration. The research results of this paper can provide necessary practical basis for the optimization of vibration and noise reduction of twin screw pump.